The power to protect : trade, health and uncertainty in the WTO - Button, Catherine (Studies in international trade law, 2004)
Examines the intersection of WTO trade liberalisation rules and domestic health protection, a subject of considerable interest to those concerned that the WTO impinges on national regulatory autonomy. It analyses the tension between health protection and trade liberalisation, and how disputes are resolved. Melbourne author.